2018
DOI: 10.1017/s0021859618000539
|View full text |Cite
|
Sign up to set email alerts
|

Classification of sugarcane varieties using visible/near infrared spectral reflectance of stalks and multivariate methods

Abstract: The use of fast and non-destructive techniques for identifying sugarcane varieties enables the development of automatic sorting systems, contributing towards improving pre-processing steps in the alcohol and sugar industries. In this context, principal component analysis (PCA), factorial discriminant analysis (FDA), stepwise forward discriminant analysis (SFDA) and partial least-squares discriminant analysis (PLS-DA) were used to classify four Brazilian sugarcane varieties based on visible/near infrared (Vis/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Vis-NIR spectroscopy may be used in a number of applications, including the classification of sugarcane varieties, with promising results [ 42 ]. The same authors showed that the spectral regions between 650 and 750 nm, corresponding to the visible spectrum, was the most suitable for sugarcane discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…Vis-NIR spectroscopy may be used in a number of applications, including the classification of sugarcane varieties, with promising results [ 42 ]. The same authors showed that the spectral regions between 650 and 750 nm, corresponding to the visible spectrum, was the most suitable for sugarcane discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…As for the varieties discrimination of apples, both back propagation neural network (BPNN) with the preprocessing of WT (49) Sugarcane contains a large amount of sugar and is a renewable energy source of biofuel, and the classification of sugarcane varieties contributes to the sugarcane breeding program. Steidle et al (96) used the VIS/NIR spectroscopy (450-1,000 nm) to measure spectral reflectance in the center of each sugarcane stalk divided area for four sugarcane varieties discrimination. PLS-DA, FDA, and SFDA using full spectra obtained the classification accuracy of 82, 81, and 74%, respectively.…”
Section: Beveragementioning
confidence: 99%
“…This technique has already been successfully used to separate batches of species in nurseries, discriminate nonvisually differentiable cultivars, and identify native tree species (Borraz-Martínez et al 2019; Neto et al 2018; Soares et al 2017; Wang and Yu 2015). In addition, the high speed of acquisition of NIR spectra, in combination with multivariate calibration techniques, has enabled the online classification (in real time) of fruits and vegetables based on quality attributes; on the other hand, when considering only the appearance of fruit, this technique has not adequately demonstrated the ability to detect differences in quality (Cunha Júnior et al 2016; Souza et al 2020).…”
Section: Introductionmentioning
confidence: 99%